Isolated neurosarcoidosis mimicking multifocal meningiomas: a diagnosis pitfall: A case report. Issue 46 (November 2016) - Wang, Kun; He, Xiaoying; Wang, Wei; Niu, Huanjiang; Wang, Yirong; Cai, Xiujun; Yang, Shuxu
Abstract: Introduction: Neurosarcoidosis accounts for approximately 5% of the sarcoidosis, which develops exclusively in the nervous system and is always difficult to diagnose. We describe a rare case of isolated neurosarcoidosis mimicking as multifocal meningiomas. A 27-year-old male was admitted to our hospital with a history of unconsciousness and convulsion 1 month ago, which was suspected as a seizure. The results showed no abnormalities in complete blood count; serum electrolytes; erythrocyte sedimentation rate and ultrasonography of the liver, pancreas, spleen, kidney and parotid gland, and so on. Chest radiograph and electroencephalogram were also normal. Serum-angiotensin-converting enzyme slightly increased. Normal opening pressure was shown in cerebrospinal fluid sampling, which includes 8/μL white blood cells, 0.93 g/L protein, and 3.03 mmol/L glucose. Enhanced magnetic resonance imaging revealed multifocal enhancement lesions, including left sphenoid wing region, left temporal and bilateral occipitoparietal region, which were suspected as multiple "meningioma". A left frontotemporal craniotomy was further performed. Both necrotizing and non-necrotizing granulomas were revealed in the pathological specimen, most of which were associated with multinucleated giant cells and macrophages. We could also see the fibrosis and inflammatory reaction in the sample composed of lymphocytes, histiocytes, and plasma cells. Histopathological examination showed that the cells were positive for human CD68 (KP1), CD68 (PGM1), and CD163; however, they were negative for the AF, epithelial membrane antigen, and glial fibrillary acidic protein. Tuberculosis-deoxyribonucleic acid test and special stains for acid-fast bacilli and fungi were negative. The diagnosis was finally made as isolated neurosarcoidosis. Then the patient was treated with additional corticosteroid therapy. Serial imaging examination 4 months later revealed that the lesions extremely decreased. Conclusion: The diagnosis of isolated central nervous system sarcoidosis was still difficult because of limitations of available diagnostic tests. So neurosarcoidosis in the clinical work should never be neglected.